Bioactive compounds from brewer´s spent grain: phenolic compounds, fatty acids and in vitro antioxidant capacity (Acta Scientiarum. Technology, 2017)
Â Brewer's spent grain (BSG) was characterized by physicochemical, total phenolic compound and flavonoids contents. Antioxidant activity was evaluated by four different assays. The chromatographic analyses were used to quantify the phenolic compounds and the fatty acids in BSG. Ethanolic extracts were tested to evaluate antibacterial activity. The higher concentration of total phenolic compounds for BSG was obtained in the extraction with ethanol 20%. BSG showed an antioxidant potential for all tests evaluated. In the case of chromatographic analysis, phenolic acids and flavonoids, such as syringic acid and catechin, respectively, were detected in high quantities. Regarding to the fatty acids profile, polyunsaturated fatty acids, such as linoleic and oleic acids, were found in significant amounts. No antibacterial activity was reported for bacterial cultures and concentrations tested. BSG may be considered a protein source, rich in fiber, polyunsaturated fatty acids and bioactive compounds with antioxidant potential.Â